Ekonomi Keluarga Peningkatan Keterampilan Ibu Rumah Tangga Melalui Pelatihan Wirausaha Berkelanjutan Berbasis Produk Lokal (Ubi Talas Ungu) Untuk Mendukung Ekonomi Keluarga - Kota Kupang - Hege, Marselinda A.; Stefanus Reinati; Kretisana Jagi; Jhon Liem; Lende Dangga; Marince Henukh; Christin M. Haba Gea; Vidensia B. Anin (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Abstract: Local products such as purple taro have great potential to be developed as a source of family income, but they remain underutilized by housewives in the GMIT Gloria Kayu Putih Congregation, Kupang City. The main problems include a lack of entrepreneurial skills, limited use of local products, and low motivation to start a business. This community service program aimed to improve the skills and independence of housewives through sustainable entrepreneurship training based on local products. The methods used included initial observation, theoretical and practical training, and evaluation through pre-test and post-test questionnaires. Results showed an increase in entrepreneurial knowledge from 25% to 85%, and 90% of participants reported greater confidence in starting a business. This training proved effective in empowering housewives to increase family income and develop businesses based on local potential.